Unveiling Anticancer Potential of COX-2 and 5-LOX Inhibitors: Cytotoxicity, Radiosensitization Potential and Antimigratory Activity against Colorectal and Pancreatic Carcinoma - Jelena Bošković; Vladimir Dobričić; Otilija Keta; Lela Korićanac; Jelena Žakula; Jelena Dinić; Sofija Jovanović Stojanov; Aleksandar Pavić; Olivera Čudina (MDPI AG, 2024)
Apart from cytotoxicity, inhibitors of the COX-2 enzyme have demonstrated additional effects important for cancer treatment (such as radiosensitization of tumor cells and cell antimigratory effects); however, the relationship between the inhibition of other inflammation-related enzyme 5-LOX inhibitors and anticancer activity is still not well understood. In our study, the cytotoxicity of thirteen COX-2 and 5-LOX inhibitors previously presented by our group (1-13) was tested on three cancer cell lines (HCT 116, HT-29 and BxPC-3) and one healthy cell line (MRC-5). Compounds 3, 5, 6 and 7 showed moderate cytotoxicity, but good selectivity towards cancer cell lines. IC50 values were in the range of 22.99-51.66 µM (HCT 116 cell line), 8.63-41.20 µM (BxPC-3 cell line) and 24.78-81.60 µM (HT-29 cell line; compound 7 > 100 µM). In comparison to tested, commercially available COX-2 and 5-LOX inhibitors, both cytotoxicity and selectivity were increased. The addition of compounds 6 and 7 to irradiation treatment showed the most significant decrease in cell proliferation of the HT-29 cell line (p < 0.001). The antimigratory potential of the best dual COX-2 and 5-LOX inhibitors (compounds 1, 2, 3 and 5) was tested by a wound-healing assay using the SW620 cell line. Compounds 1 and 3 were singled out as compounds with the most potent effect (relative wound closure was 3.20% (24 h), 5,08% (48 h) for compound 1 and 3.86% (24 h), 7.68% (48 h) for compound 3). Considering all these results, compound 3 stood out as the compound with the most optimal biological activity, with the best dual COX-2 and 5-LOX inhibitory activity, good selectivity towards tested cancer cell lines, significant cell antimigratory potential and a lack of toxic effects at therapeutic doses.